An explorative investigation on the sustainability of knowledge repository establishment : the case of Malaysian public sector / Raja Faralita Raja Mohamad and Siti Arpah Noordin - Raja Mohamad, Raja Faralita; Noordin, Siti Arpah (Faculty of Information Management, 2014)
Knowledge is an important resource in this current economic condition where organizations are competing in creating more innovation in order to sustain their business capabilities in the market. Therefore, it is crucial for an organization to preserve their knowledge as knowledge is a source of competitive advantage in this current era. An organization needs to plan and design the most appropriate approach to enable knowledge to be captured, stored and fully utilized. This study will focus on the sustainability of Knowledge Repository establishment in sharing the technical knowledge of the key personnel from the Malaysian public sector. The objective of this paper is to propose a research framework of an explorative investigation of the sustainability elements of an institutional repository establishment in the Malaysian public sector. The study will explore the dynamics of the repository that are used by the technical personnel in capitalizing the organizational technical knowledge by contributing, retaining and applying the knowledge asset. The research framework which governs the scope of study will explore the elements that may have significant influences towards the sustainability of the institutional repository.